A review on production of polyhydroxyalkanoate (PHA) biopolyesters by thermophilic microbes using waste feedstocks. (December 2021) - Chavan, Shraddha; Yadav, Bhoomika; Tyagi, R.D.; Drogui, Patrick
Graphical abstract: Highlights: Comprehensive summary of thermophilic PHA producers using waste feedstocks. Thermophiles are potential microbes for economic pilot-scale PHA production. Methods for efficient selection of thermophilic PHA producers are discussed. Challenges in the bioprocess are addressed along with the present research gaps. Abstract: Polyhydroxyalkanoates (PHAs) are produced by numerous microbes as a subcellular energy source. Despite of their diverse applications, exorbitant production cost limits their commercial synthesis. Apart from various cost determining factors such as cost-effective feedstocks or economic recovery methods, the use of appropriate bacteria holds the key to reduce the fermentation economics. Extremophiles, especially thermophilic PHA producers, could make the bioprocess economically viable by reducing the production cost in several aspects. Using variety of waste feedstocks as carbon substrates could open the way for the valorisation of industrial waste streams and cost-effective PHA production. Therefore, the article critically reviews the current knowledge of the synthesis of PHA polyesters in thermophilic conditions. Additionally, it summarises several studies on thermophilic PHA producing bacteria grown on various waste substrates. To conclude, the paper focuses on screening and recovery methods as well as technical challenges in thermophilic PHA production.